Case report of misdiagnosis: a rare case of hepatic epithelioid hemangioendothelioma characterized primarily by fever - Zhao, Jian; Dang, Yanli (Frontiers in Oncology, 2025)
This study reports a case of a 47-year-old female who was initially misdiagnosed as having liver abscess due to repeated fever, and was later misdiagnosed again as liver inflammatory myofibroblastic tumor(IMT) after liver biopsy. After surgical removal, molecular pathological examination confirmed the diagnosis of Hepatic epithelioid hemangioendothelioma(HEHE). HEHE with fever as the main symptom is extremely rare and there are no similar reports available at present. This study summarizes the key points of HEHE diagnosis and treatment, analyzes the reasons for the misdiagnosis in this case and the possible factors causing the fever symptoms, highlights the difficulties in HEHE diagnosis and the significant value of molecular pathology in its diagnosis.